Folklore Elements in the Contemporary Novel Óštrigéca by Marjan Tomšič - Tucovič Sturman, Vladka (Studia mythologica Slavica, 2022)
The paper discusses the use of folkloric elements, more specifically supernatural beings and elements of folk medicine and Christianity in a contemporary Slovene novel Óštrigéca (1991) by Marjan Tomšič. The novel is part of the writer's Istrian opus and is generally considered as the one that placed the region of Slovene Istria on the Slovene literary map and introduced dialectal and folkloric elements into contemporary Slovene literature. The study was conducted using the interdisciplinary approach with the method of literary and folkloric analysis.